A morte e suas representações na sociedade: a arte em desvelar o Cemitério São João Batista/RJ como atrativo turístico - Monteiro, Jaqueline de Oliveira (2017)
The death is a fact present all cultures. What differs them is the symbolism connected to each society throughout centuries, manifested though signs. In this universe, tombs art plays the role of perpetrator agent of the history, denoting symbols ans costumes of differents periods. To observe 'the city of the deads' is to unveil the synthetised way the preferences that some symbols were chosen by the loved ones so to represent the dead immortalize their memory before the time. To understand the nuances of this niche is the function of the touristic activity that by fragmenting a new touristic idea, will be able to understand it's imbrications, there for, attend the needs and expectations of those consumers. The work consistes in analize the cemitery São João Batista as a tourism potential through qualitative researches, beyond if the experienced interpretation of the author in a City Tour in the studied necropoli.